ANALISIS PEMERINGKATAN KINERJA DENGAN PERSPEKTIF BALANCED DETERMINAN BUSNIESS TO CONSUMER (B2C) E-COMMERCE DI KOTA MATARAM - Risa Marchidita; Nurabiah Nurabiah; Baiq Anggun Hilendri L (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2017)
The objective of this study is to examine the influence of lifestyle, trust, perception of risk, perception of ease, perception of benefits, perception of control, customer satisfaction and customer loyalty toward the business to consumer e-commerce system. This study was conducted in Mataram City by targeting online shopping user as research sample. The data used in this study is collected through the distribution of questionnaire with 100 respondents divided into several clusters of dissemination. The results of this study indicate that trust, perception of ease and customer loyalty significantly influence business to consumer e-commerce system. Meanwhile, other variables such as lifestyle, risk perception, benefit perception, control perception and customer’s satisfaction do not affect business to consumer e-commerce system. This study implies that business to consumer e-commerce systems system needs to be improved both in terms of ease and security in the transaction in order to maximize the system in online shopping transactions.